2010
DOI: 10.1001/archinternmed.2010.349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Physician Comanagement of Hypertension and Reduction in 24-Hour Ambulatory Blood Pressures

Abstract: Background Pharmacist-physician co-management of hypertension has been shown to improve office blood pressures (BP). We sought to describe the effect of such a model on 24-hour ambulatory BPs. Methods We performed a prospective, cluster-randomised controlled clinical trial in 179 patients with uncontrolled hypertension from five primary care clinics in Iowa City, Iowa. Patients were randomized by clinic to receive pharmacist-physician collaborative management of hypertension (intervention) or usual care (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 29 publications
5
69
2
1
Order By: Relevance
“…Although there was no control group, this magnitude is greater than the SBP reductions in control groups of 7 other studies using health coaching, which ranged from 2 to 14 mm Hg. [12][13][14][15][16][17][18] Patients had an average of 0.9 fewer primary care offi ce visits in the 6-month study period compared with the 6 months before the study, and this difference was maintained in the 6 months after the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no control group, this magnitude is greater than the SBP reductions in control groups of 7 other studies using health coaching, which ranged from 2 to 14 mm Hg. [12][13][14][15][16][17][18] Patients had an average of 0.9 fewer primary care offi ce visits in the 6-month study period compared with the 6 months before the study, and this difference was maintained in the 6 months after the study.…”
Section: Discussionmentioning
confidence: 99%
“…10 When compared with usual care, the combination of home monitoring with home titration of antihypertensive medications is associated with better blood pressure control. 11 Using nurses or pharmacists to coach patients and assist in home titration reduces blood pressure compared with usual care, [12][13][14][15][16][17][18] but these changes involve expensive health care professionals rarely present in primary care.…”
Section: He a Lt H Coaching A Nd Hy Per T Ensionmentioning
confidence: 99%
“…12 Some studies have shown that pharmacist participation in designing, implementing, and monitoring therapeutic programs in patients with CVD or CV risk factors could (a) improve the patient's knowledge, 13 (b) facilitate adoption of and outcomes from lifestyle interventions, 14 (c) improve the identification of candidates and the results of primary 15 or secondary 16 prevention, and (d) increase the percentage of patients with high CV risk who achieve the goals related to BP [17][18][19][20] and lipid 9,21 levels. In contrast, other randomized controlled trials (RCTs) have found that community pharmacist intervention did not lead to improvements in primary outcome measures (e.g., hospital admissions 22 or the proportion of patients receiving appropriate medication 23 ).…”
Section: Effectiveness Of Dader Methods For Pharmaceutical Care On Conmentioning
confidence: 99%
“…Zhao et al 49 and the results of the clinical therapy eventually. Green et al (2008) and Weber et al (2010) studies showed that pharmacist-physician co-management team can improve control blood pressures and 24 h ambulatory blood pressures. How to improve the medication compliance of the patients decides whether the patients can get a systematical and long-period treatment, and whether the blood pressure can be maintained at a controllable level; thereby, the probability of complications can be reduced.…”
mentioning
confidence: 99%